Main St. in Nome, probably between 1899 and 1900 - Warner, Arthur Churchill, 1864-1943 (1899)
Gold was discovered on the Nome beaches in the Summer of 1899. By Spring of 1900, thousands had arrived for the gold rush. Signs on buildings include The Reception, The Cabinet, S.F. Store, Dentist--Painless Extraction, The Grotto, and F.W. Mettler, Attorney at Law Frank W. Mettler was born in 1867 in Illinois. Before moving to Alaska in 1899, he lived in Ft. Benton, Washington. In 1900 he was living in Nome and working as an attorney. He was married, but his family was not with him. By 1910, he was living in Helena, Montana, with his wife and three children, still working as an attorney. Warner 144 Filed in Alaska series.